THE IMPROVEMENT OF MSMEs' BUSINESS PERFORMANCE DURING THE COVID-19 PANDEMIC THROUGH FINANCIAL AND DIGITAL LITERACY - Athia, Ita; Soetjipto, Budi Eko; Efendi, Erfan (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
The pandemic has impacted the global economy, includingMSMEs,especially in financial issues such as minimal revenue flow and inadequate financial management. On the marketing side, there has been a decrease in demand due to the implementation of social restrictions, which will affect the company"™s existence. Therefore, MSMEs need to adapt by transforming to online marketing. Improved financial and digital literacy can enhance MSME performance. This study aims to determine the moderating effect of financial literacyanddigital literacyamongMSMEs inimprovingtheir businessperformance. A Quantitative research method with Partial Least Square (PLS) was used to analyze the data. The results show that financial management and digital marketing have a direct effect on MSMEs"™ performance. Furthermore, financial literacy can moderate and improve the performance of MSMEs, whereas digital literacy cannot effectively moderate the implementation of digital marketing to improve MSMEs"™ performance. This study implies that MSMEs must improve their financial behavior and decision-making during crises and enhance their knowledge and skills in managing digital marketing.JEL: L250, M310, G41.